Potensi Antioksidan Ekstrak Kombinasi Air-Etanol Pada Simplisia Selada Air (Nasturtium officinale R. Br) - Karina Tria Amanda; Sentot Joko Raharjo (LPPMKI - AKAFARMA AKFAR PIM, 2022)
Empirically, selada air has a potency as a vegetable rich in antioxidants, but there has been no study of the antioxidant activity potency of selada air simplisia maceration with water-ethanol combination solvent. This study aims to determine the optimization of yield and antioxidant activity (IC50 value) of selada air simplisia maceration using ethanol-water combination solvent. The method of this research is the determination of the yield and IC50 value using the DPPH method from the maceration of selada air using a water-ethanol combination solvent (96, 70, 30 and 0%). The yields of selada air simplisia maceration with water-ethanol combination solvent (96, 70, 30 and 0%) are 9.25±1.62%, 15.63±1.25%, 23.63±2.38% and 19.99±3.82%. The IC50 values ​​are 613.77±1.90 ppm, 190.892±5.41 ppm, 350.78±1.77 ppm, and 2418.59±137.80 ppm. In conclusion, the optimal yield of maceration result is shown by the water-ethanol combination solvent of 30% (23.63%) and the optimal IC50 value is shown by the water-ethanol combination solvent of 70% (190.892 ppm).